Reservoirs and vectors of emerging viruses - MacKenzie, John; Jeggo, Martyn (Elsevier, 2013)
Wildlife, especially mammals and birds, are hosts to an enormous number of viruses, most of which we have absolutely no knowledge about even though we know these viruses circulate readily in their specific niches. More often than not, these viruses are silent or asymptomatic in their natural hosts. In some instances, they can infect other species, and in rare cases, this cross-species transmission might lead to human infection. There are also instances where we know the reservoir hosts of zoonotic viruses that can and do infect humans. Studies of these animal hosts, the reservoirs of the viruses, provide us with the knowledge of the types of virus circulating in wildlife species, their incidence, pathogenicity for their host, and in some instances, the potential for transmission to other hosts. This paper describes examples of some of the viruses that have been detected in wildlife, and the reservoir hosts from which they have been detected. It also briefly explores the spread of arthropod-borne viruses and their diseases through the movement and establishment of vectors in new habitats.